Pendekatan Kearifan Lokal pada Aspek Sosial di Wisata Malam Kota Berastagi - Veronica, Selly; Ginting, Nurlisa; Marisa, Amy (Jurnal ABDIMAS PARIWISATA, 2020)
Local Wisdom Approach on Social Aspect in Berastagi Night Tourism. Tourism is a strategic aspect that becomes a significant part of urban development. Night tourism is the kind of tourism which innovative and potential to develop. Berastagi is one of the popular tourist attractions in North Sumatra that has night tourism destinations. But nowadays, the negative image of night tourism that attaches to community life always be the obstacle in its developing process. Approaching the local wisdom in the night tourism social aspect is necessary to be held to create harmony between the night tourism and community. The descriptive qualitative analysis has been carried out with study the data from depth interview and field observation. This study shows local wisdom be the strength and protection that the community has to support the night tourism development in Berastagi